A review of the Palaearctic Mniotype adusta (Esper, 1790) species-group with description of a new species and six new subspecies (Lepidoptera: Noctuidae) - Volynkin, Anton V.; Matov, Alexei Yu.; Behounek, Gottfried; Han, Hui-Lin (Zootaxa, 2014)
Eighteen Palaearctic taxa of the Mniotype adusta species-group are reviewed. One new species (M. kobyakovi Volynkin, Matov & Behounek, sp. n.) and six new subspecies (M. lama kortka Volynkin, Matov & Behounek, ssp. n., M. lama etugen Volynkin, Matov & Behounek, ssp. n., M. lama ayubaevorum Volynkin, Matov & Behounek, ssp. n., M. adusta poltavskyi Volynkin, Matov & Behounek, ssp. n., M. adjuncta cineritia Volynkin, Matov & Behounek, ssp. n. and M. dubiosa amitayus Volynkin & Han, ssp. n.) are described. Two taxa, previously regarded as subspecies are restored to specific status: M. adjuncta (Moore, 1881) stat. n. and M. dubiosa (A. Bang-Haas, 1912) stat. n. A taxon previously regarded as a junior synonym is restored to specific status: M. juldussica (Draudt, 1934) stat. n. A new synonymy is introduced: M. bathensis (Lutzau, 1900) = Hadena adusta var. moesta Staudinger, 1897 syn. n. The synonymy of M. bathensis and Crino adusta subsp. urupino Bryk, 1942 syn. rev. is revised. The lectotypes for Hadena? lama Staudinger, 1900, Mamestra vicina Alphéraky, 1882, Hadena adusta var. moesta Staudinger, 1897 and Hadena lama var. dubiosa A. Bang-Haas, 1912 are designated. The neotype for Crino adusta juldussica Draudt, 1934 is designated. The adults, male and female genitalia of all reviewed species and subspecies are illustrated.